Message-Optimal Algorithm for Detection and Resolution of Generalized Deadlocks in Distributed Systems - Srinivasan, S.; Rajaram, R. (Informatica)
Message-Optimal Algorithm for Detection and Resolution of Generalized Deadlocks in Distributed Systems